(untitled) (Critical Journal of Social Sciences, 2026)
The current rapid development of artificial intelligence presents an unprecedented challenge to legal scholarship, revealing fundamental flaws in the methods of its regulatory studies. This paper examines the institutional constraints that hinder the generation of rigorous, relevant, and equitable legal research on AI governance. Using a mixed-methods sequential explanatory design with a combination of systematic legal analysis, a global survey of legal scholars (N=164), and in-depth interviews (n=22), the study diagnoses a synergistic crisis. The results expose that temporal misalignment (2.3-year lapse between technical and legal developments), interdisciplinary inattention, jurisdictional fracture, and doctrinal uncertainty are not isolated agents. Rather, they interrelate together to multiply their adverse impact, forming a vicious circle of scholarly obsolescence and irrelevance as legal analysis tends to deal with technologies that are already obsolete. With the Feminist Legal Theory and Victimology application, it is possible to see how these structural failures victimize early-career scholars and Global South scholars in disproportionate numbers and serve as a systemic form of academic injustice that constrains different views on how to shape governance. The paper finds the paradigm of legal research systematically deficient in its capacity to govern the algorithmic mind, since even its own institutional and methodological frameworks reinforce continuity and exclusion. This study forms a new theory to explain this deep methodological crisis and makes a desperate appeal to create nimble, interdisciplinary, and critically self-reflective research paradigms. The paradigm shift is needed to put the legal study back on course to keep pace with the pace, complexity, and globalization of technological change so that the law can be used to its best advantage and reduce the risks of AI.